Effect of exenatide on cholecystokinin-induced gallbladder emptying in fasting healthy subjects - Keller, Jutta; Trautmann, Michael E.; Haber, Harry; Tham, Lai San; Hunt, Tamsin; Mace, Kenneth; Linnebjerg, Helle (Regulatory peptides, 2012)
Exenatide is a glucagon-like peptide-1 receptor agonist for the treatment of type 2 diabetes and has been shown to lower blood glucose through multiple mechanisms, including glucose-dependent insulin secretion, suppression of postprandial glucagon release and slowing of gastric emptying. The effects of exenatide on biliary motility are unknown. This study evaluated the effect of a single dose of exenatide on cholecystokinin (CCK)-induced gallbladder emptying. Healthy subjects participated in this randomized, 2-period, double-blind crossover study. Fasting subjects received a single subcutaneous injection of exenatide (10μg) or placebo 60min before CCK infusion. Gallbladder volume and ejection fraction (EF) were assessed by ultrasonography before, during, and after CCK infusion (0.003μg/kg infused over 50min at 2mL/min). The diameters of the main pancreatic duct and common bile duct were measured sonographically at the same time points before, during, and following CCK infusion. Administration of exenatide did not affect pre-CCK infusion gallbladder volume or EF compared to placebo. During the CCK-infusion, the mean minimum gallbladder volume was similar for exenatide (13.68mL) and placebo (11.05mL) (least squares mean [LSM] difference of 2.62mL; 95% confidence interval [CI], −0.53, 5.78), but the mean maximum EF was lower for exenatide (28.79%) versus placebo (46.13%) (LSM difference of −17.34%; 95% CI, −30.54, −4.13). Exenatide had no clinically significant effects on pancreatic or bile duct diameters. In conclusion, exenatide reduced CCK-induced gallbladder emptying compared with placebo in fasting healthy subjects. ► This study evaluated the effects of exenatide on fasting CCK-induced gallbladder emptying. ► Exenatide did not affect pre-CCK gallbladder volume or ejection fraction. ► With CCK, exenatide decreased ejection fraction but not gallbladder volume. ► Exenatide did not affect pancreatic or bile duct diameters. ► Exenatide reduced CCK-induced gallbladder emptying compared to placebo.